Patient expectations are better for immunotherapy than traditional chemotherapy for cancer - Ihrig, Andreas; Richter, Jenniffer; Grüllich, Carsten; Apostolidis, Leonidas; Horak, Peter; Villalobos Bollen, Matthias Americo; Grapp, Miriam; Friederich, Hans-Christoph; Maatouk, Imad (Journal of cancer research and clinical oncology, 2020)
The main aim of the study was to explore the expectations and knowledge of advanced-stage cancer patients about immunotherapy.
Gesehen am 25.11.2021